Formations of Feminist Strike: Connecting Diverse Practices, Contexts, and Geographies - Neuman Stanivukovic, Senka; Robbe, Ksenia; Thomas, Kylie (Atlantis, 2023)
This introduction to the special issue on Feminist Strike takes up the question of what remains marginalized and overlooked within dominant discourses on contemporary feminist protests. Drawing on experiences of and approaches to feminist refusal that involve questions of labour, we propose the ways in which conceptualizations of feminist strike can be employed as a lens to build a conversation between different practices, scales, and geographies, particularly across postcolonial and postsocialist contexts. Through a reading of Aliki Saragas’s film Strike a Rock (2017) about the women living around the Marikana miners’ settlement in the aftermath of a major strike, we explore how notions of feminist strike can be expanded by situating Black women’s struggles in South Africa within a long tradition of women’s resistance and showing how political resistance is bound to questions of reproductive work. To understand the intersection of postsocialist, post-conflict, and (pre-)Europeanization transformations, we consider the case of a large-scale strike and public demonstrations against the bankruptcy of the Croatian shipyard Uljanik that took place in 2018 and 2019. Our perspectives on the Marikana and the Uljanik strikes show how women in both places practise a politics of refusal and resistance against ruination, violence, and defeat. In the last section, we summarize the contents of the articles that comprise the special issue.